دور عمليات إدارة المعرفة في تعزيز الميزة التنافسية : دراسة تحليلية لآراء عينة من المديرين في عدد من المنظمات الصناعية /نينوى - د. ناهدة اسماعيل عبدالله (PROSPECTIVE RESEARCHES, 2023)
This research aims at determining the role of knowledge management operations in reinforcing competitive privilege and its identification. According to a sample based on hypothetical type taking into consideration the nature and the variables of the research and their dimensions. This is represented by knowledge management operations, i.e generating, storing, distribution and application. The competitive advantage includes the strategy of the lowest cost, the strategy of differentiation and the strategy of concentration. Accordingly, two main hypotheses have been put from which more sub-sectional hypotheses will appear. In order to choose the hypotheses, we depend on a series of statistical methods. The paper concludes some important conclusions which support the hypotheses and some recommendations which concentrate on the role of knowledge management operation in the reinforcement of competitive advantage.